Moral Reasoning Enables Developmental and Societal Change. (November 2021) - Killen, Melanie; Dahl, Audun
Moral reasoning is an essential part of how humans develop and a fundamental aspect of how human societies change over time. On a developmental timescale, reasoning about interpersonal disagreements and dilemmas spurs age-related changes in moral judgments from childhood to adulthood. When asked to distribute resources among others, even young children strive to balance competing concerns with equality, merit, and need. Over the course of development, reasoning and judgments about resource distribution and other moral issues become increasingly sophisticated. From childhood to adulthood, individuals not only evaluate acts as right or wrong but also take the extra steps to rectify inequalities, protest unfair norms, and resist stereotypic expectations about others. The development of moral reasoning also enables change on a societal timescale. Across centuries and communities, ordinary individuals have called for societal change based on moral concerns with welfare, rights, fairness, and justice. Individuals have effectively employed reasoning to identify and challenge injustices. In this article, we synthesize recent insights from developmental science about the roles of moral reasoning in developmental and societal change. In the concluding section, we turn to questions for future research on moral reasoning and change.